On lapped splices in high-strength steels - Experimental investigations and damage-mechanical simulations ... - Eyben, Felix; Bartsch, Helen; Feldmann, Markus (RWTH Aachen University, 2024)
NORDIC STEEL 2024 : the 15th Nordic Steel Construction Conference, June 26-28, 2024, Luleå, Sweden 15. Nordic Steel Construction Conference, Nordic Steel 2024, Luleå, Sweden, 26 Jun 2024 - 28 Jun 2024; [Stockholm] : The Swedish Institute of Steel Construction 1-10 (2024). doi:10.5281/ZENODO.12192498 ... : Published by The Swedish Institute of Steel Construction, [Stockholm] ...